Design and Analysis of Different Line-Start PM Synchronous Motors for Oil-Pump Applications - Tingting Ding; Takorabet, N.; Sargos, F.-M.; Xiuhe Wang (IEEE transactions on magnetics, 2009)
This paper presents a comparison between three architectures of line-start PM motors for oil-pump application. This paper is focused on the performances in synchronous operation as well as the self-starting operations. Effects of electrical parameters on the starting and steady performance characteristics are demonstrated to find a satisfying design to meet required performances, it seems that the interior permanent magnet motor yields an impressive starting performance.